Be Aware of Inequality: Political Challenges and Redistributive Public Policies - Suaib, Eka; Husein, Najib; Santoso, Dodi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This article focused to uncover inequalities in natural resource management. The presence of a mining business in a region is dilemmatic. On one hand, it can be a blessing because regions need investment in order to boost regional income because companies can provide royalties to the government that grants permits, both to the regional government, provincial government, and district/city government. This is not to mention various taxes such as land rent, buildings, and other taxes. However, in terms of equality, especially in local community, a mining company discriminates and acts unfairly. The community stated that the mining company had no impact on welfare. The second dilemma is implicated in more inclusive development to reduce inequalities in the context of democracy. So far, studies on mining have been carried out by scientists from various perspectives such as mining, mining and investment governance, social conflicts in the mining sector, the impact of the mining sector on environmental damage, natural wealth in the mining sector, natural resources curse, and political economy of mining sector. Based on various studies above, scientists have not much attention to the dynamic aspects between mining management and the enforcement of citizenship rights. This study found the novelty, that in the context of regional autonomy which gives freedom to the regions and actors to manage natural wealth. By using a public policy perspective, this study found that the importance of policy making so that there is equality of rights. It is hoped that vulnerable and marginal groups can help to reduce inequality, especially on gaps that occur from time to time.